HUBUNGAN JENIS KELAMIN DAN FREKUENSI HEMODIALISA DENGAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA DI RUMAH SAKIT UMUM DAERAH RADEN MATTAHER JAMBI - Astri Ipo; Tuti Aryani; Marta Suri (Universitas Baiturrahim, 2016)
Background: Chronic renal failure is a chronic disorder of renal function is progressive and irreversible, which can result in physiological changes that can not be addressed again by conservatives, but by way of renal replacement therapy. Renal replacement therapy is one that is hemodialysis, which is a treatment that must be followed for life and can not heal or restore kidney disease, but at least it can improve the quality of life for patients undergoing hemodialysis. According to WHO chronic renal failure patients undergoing hemodialysis in the world an estimated 1.4 million people with an incidence of 8% per annum. The aim of this study was to determine the relationship sex and frequency of hemodialysis with the quality of life of patients with chronic renal failure undergoing hemodialysis in the hemodialysis room Raden Mattaher Jambi Hospital.Method:This research is a quantitative research with cross sectional approach. Data analysis techniques in this study using the analysis of univariate and bivariate statistical test Chi-square. This study was conducted in 24-July-August 7, 2015. The population of as many as 1039 with a total sample of 89 respondents with accidental sampling sampling techniques.Result: Statistical test results obtained P-value = 0.000 (p <0.05), which means that there is a significant relationship between sex and the quality of life of patients with chronic renal failure undergoing hemodialysis, and there was a significant association between the frequency of hemodialysis with the quality of life of patients with kidney failure undergoing chronic hemodialysis, results obtained statistical test P-value = 0.010 (p <0.010).To the Raden Mattaher Jambi Hospitals is expected to make a policy for adding facilities, such as indoor and hemodialysis equipment, so it can support optimal service delivery, particularly for patients undergoing hemodialysis in order to improve the quality of life